The Effect of Using Loose Part Media on Early Literacy Skills of 4-5 Year Old Children - Rinda Aulia Ramadhanti; Evie Palenewen; Fachrul Rozie (CV. Edujavare Publishing, 2026)
Early childhood is a child who has an age range from 0 to 6 years. Early life only comes once in every person's life stages. So, the existence of early age should not be wasted. This study aims to determine the effect of the use of loose part media on the early literacy ability of children aged 4-5 years at Al Raudah Samarinda Kindergarten. This type of research is quantitative with a pre-experimental approach method with a one-group pretest-posttest design research model. The subjects of this study are 19 students of Al Raudah Samarinda Kindergarten. The research instruments used include tests from pretest and posttest observation sheets in the form of statement instruments equipped with documentation. The data analysis technique used is data obtained from the N-Gain test. The results showed that the N-Gain test > 0.7 with a percentage of 0.83 or included in the high category, which means that the loose part media for children's early literacy ability is in the effective category. Thus, it means that there is an increase in effectiveness between pretest and posttest so that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, meaning that there is an effect of the use of loose part media on early literacy ability in children aged 4-5 years at Al Raudah Samarinda Kindergarten.